Multiple patterns of persistent inward currents with multiple types of repetitive firings in medullary serotonergic neurons of mice: An experimental and modeling study. - Yi Cheng; Xingyu Wang; Qiang Zhang; Renkai Ge; Mei Zhou; Yue Dai (PLoS Computational Biology)
Persistent inward currents (PICs) play a crucial role in regulating neuronal excitability. These currents are composed of calcium (CaL) and sodium (NaP) components in vertebrate spinal neurons. Recent studies have reported that PICs are expressed in serotonergic neurons (5-HT) in medulla of mice. Multiple patterns of PICs were identified in 5-HT neurons, corresponding to a range of distinct repetitive firing types. The mechanisms underlying formation of these PIC patterns and firing types remain unknown. Using combined modeling and experimental approaches we explored the ionic mechanisms responsible for the PIC patterns and firing types. The whole cell patch clamp recordings were performed on the medullary 5-HT neurons of postnatal day 3-6 mice. A 5-HT neuron model was built based on the membrane properties of the 5-HT neurons and kinetics of voltage-gated channels. Results from physiological experiments and modeling simulations included: (1) PICs in 5-HT neurons were classified into six patterns based on their current trajectory induced by bi-ramp voltage, while repetitive firings were categorized into three types according to their response to bi-ramp current. Modulation of PICs conductance and kinetics altered the PIC patterns and firing types. (2) NaP conductance contributed to amplitude of PICs, whereas the slow inactivation gate (Sgate) of NaP regulated the PIC patterns and firing types. Increasing Sgate changed trajectory of PICs from counterclockwise to clockwise and firing types from asymmetrical to symmetric types induced by bi-ramp current. (3) CaL conductance dominated the amplitude of PICs, while CaL kinetics (half-activation voltage and slope) determined inactivation of PICs and prolongation of repetitive firing. (4) The novel finding was that distribution of CaL in distal dendrites modulated the PIC patterns and firing types. This study provides insights into the ionic mechanisms underlying generation of multiple PIC patterns and firing types in 5-HT neurons.